Laser-induced multiple ionization of molecular ion beams: N2+, CO+, NO+, and O2+ - Gaire, B.; McKenna, J.; Johnson, Nora G.; Sayler, A. M.; Parke, E.; Carnes, K. D.; Ben-Itzhak, I. (My University, 2009)
We have simultaneously measured the kinetic energy release and the angular distributions for the multiply charged fragmentation of diatomic molecular ions, N2+, CO+, NO+, and O2+, in intense ultrashort laser pulses. Using a coincidence three-dimensional momentum imaging method we unambiguously separate all fragmentation channels, including dissociation, since we measure both neutral and ionic products. Based on the experimental results, we conclude that the fragmentation mechanism that explains the multielectron dissociative ionization of these molecular ions entails a stairstep process. This mechanism, which involves stretching the molecules prior to each sequential ionization step, is similar to that proposed in some earlier studies that use neutral molecules as targets. We find that structure in the breakup of the molecules to lower charge states is molecule specific, while, for breakup to higher charge states, all species tend to follow a universal trend.